Counseling On Sport Massage and Use of Kinesiotaping For Athletes and Gymnastic Coaches - Tresnowatii, Idah; Gilang Nuari Panggraita; Mega Widya Putri; Lukman Alfaris; Nurul Aqil Nahari (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Sport Massage is a method of recovery using massage specifically for athletes. Sports injuries that occur in performance sports athletes, apart from disrupting their health, can also reduce the athlete's opportunity to achieve optimally. Massage is a form of manipulation that has the characteristics of the causes of sports injuries, types of injuries and how to treat sports injuries. The ultimate goal of treating sports injuries is to maximize the injury recovery process and to minimize the risk of re-injury. Sports injuries are injuries to the integumentary, muscular and skeletal systems caused by sports activities. One of the branches of sport that aims to achieve achievement is gymnastics. Gymnastics is divided into 3: Artistic Gymnastics, Rhythmic Gymnastics and Aerobic Gymnastics. Training aimed at achieving maximum performance certainly has risks. The risk of sports activities is injury, ranging from minor injuries to serious injuries which are very likely to occur in athletes who do regular exercise.